Pengaruh Pembelajaran Prototipe Terhadap Kemandirian Siswa Kelas V UPT SPF SDN 106157 Tahun Ajaran 2022/2023 - Muthalib, Muthalib; Ramadhan, Nuri; Malinda, Leni (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This research investigates the effect of Prototype Learning (X) on student independence (Y) in class V at UPT SPF SDN 106157 during the 2022/2023 academic year. The study uses an experimental method to analyze the relationship between the Prototype Learning model and students' independence. The results demonstrate that Prototype Learning falls into the "good" category, with students' independence similarly categorized as "good," achieving an average score of 82.2 in the experimental class. Students who utilized Prototype Learning recorded an average independence test score of 82.2 with a standard deviation of 9.06, while those in the control group who did not use the model achieved an average score of 51.67 with a standard deviation of 7.18. The hypothesis testing showed a t-value (th) of 0.06, which was compared with the critical t-table value of 0.245 at a 5% significance level for N = 60. Since 0.245 > 0.06, the hypothesis that Prototype Learning positively impacts student independence is accepted. This finding suggests that Prototype Learning is an effective method for enhancing student independence, providing a structured and supportive learning environment that fosters personal growth and academic success.